Investigations into N-Sulfinyl Imino Esters as Versatile Reagents for the Synthesis of N-Sulfinyl Compounds and Unnatural α-Amino Acid Derivatives - Goodrich, Oliver H. (2023)
N-Sulfinylimino esters are a highly versatile class of compounds, they are already widely used within the pharmaceutical industry for the preparation of chiral α-amines. This work further explores their use as versatile reagents for the synthesis of unnatural α-amino acid derivatives and novel cyclic sulfinamides.